Association of jasmonic acid priming with multiple defense mechanisms in wheat plants under high salt stress - Sheteiwy, Mohamed S.; Ulhassan, Zaid; Qi, Weicong; Lu, Haiying; AbdElgawad, Hamada; Minkina, Tatiana; Sushkova, Svetlana; Rajput, Vishnu D.; El-Keblawy, Ali; Jośko, Izabela; Sulieman, Saad; El-Esawi, Mohamed A.; et al. (Frontiers in Plant Science, 2022)
Salinity is a global conundrum that negatively affects various biometrics of agricultural crops. Jasmonic acid (JA) is a phytohormone that reinforces multilayered defense strategies against abiotic stress, including salinity. This study investigated the effect of JA (60 μM) on two wheat cultivars, namely ZM9 and YM25, exposed to NaCl (14.50 dSm−1) during two consecutive growing seasons. Morphologically, plants primed with JA enhanced the vegetative growth and yield components. The improvement of growth by JA priming is associated with increased photosynthetic pigments, stomatal conductance, intercellular CO2, maximal photosystem II efficiency, and transpiration rate of the stressed plants. Furthermore, wheat cultivars primed with JA showed a reduction in the swelling of the chloroplast, recovery of the disintegrated thylakoids grana, and increased plastoglobuli numbers compared to saline-treated plants. JA prevented dehydration of leaves by increasing relative water content and water use efficiency via reducing water and osmotic potential using proline as an osmoticum. There was a reduction in sodium (Na+) and increased potassium (K+) contents, indicating a significant role of JA priming in ionic homeostasis, which was associated with induction of the transporters, viz., SOS1, NHX2, and HVP1. Exogenously applied JA mitigated the inhibitory effect of salt stress in plants by increasing the endogenous levels of cytokinins and indole acetic acid, and reducing the abscisic acid (ABA) contents. In addition, the oxidative stress caused by increasing hydrogen peroxide in salt-stressed plants was restrained by JA, which was associated with increased α-tocopherol, phenolics, and flavonoids levels and triggered the activities of superoxide dismutase and ascorbate peroxidase activity. This increase in phenolics and flavonoids could be explained by the induction of phenylalanine ammonia-lyase activity. The results suggest that JA plays a key role at the morphological, biochemical, and genetic levels of stressed and non-stressed wheat plants which is reflected in yield attributes. Hierarchical cluster analysis and principal component analyses showed that salt sensitivity was associated with the increments of Na+, hydrogen peroxide, and ABA contents. The regulatory role of JA under salinity stress was interlinked with increased JA level which consequentially improved ion transporting, osmoregulation, and antioxidant defense.